Hepatic metabolism of licochalcone A, a potential chemopreventive chalcone from licorice (Glycyrrhiza inflata), determined using liquid chromatography-tandem mass spectrometry - Huang, Lingyi (Anal Bioanal Chem, 2017)
The metabolism of the chemoprevention agent licochalcone A, which is a chemopreventive chalcone found in abundance in the licorice species Glycyrrhiza inflata, was investigated using human liver microsomes and human hepatocytes combined with analysis using high performance liquid chromatography-mass spectrometry (LC-MS). Five oxygenated phase I metabolites of licochalcone A were formed by human liver microsomes, including a catechol on the A-ring, two intramolecular cyclization products following epoxidation of the exocyclic alkene at position 5 of the B-ring, and two dioxygenated products. Nine phase II monoglucuronides of licochalcone A and its oxygenated phase I metabolites were formed during incubation with human hepatocytes. These included (E)-licochalcone A-4-glucuronide, (E)-licochalcone A-4’-glucuronide, (Z)-licochalcone A-4-glucuronide, glucuronic acid conjugates of all of the monooxygenated phase I metabolites, and glucuronides of the licochalcone catechol after methylation by catechol-O-methyl transferase. In addition, human hepatocytes formed one sulfate conjugate and one glutathione conjugate of licochalcone A. The structures of all major metabolites were determined using a combination of accurate mass measurement, LC-tandem mass spectrometry, LC-UV, nuclear magnetic resonance, and comparison with standards. The cytochrome P450 enzymes and UDP-glucuronosyltransferases responsible for the formation of the major metabolites were identified. Based on in vitro hepatic clearance calculations, licochalcone A is predicted to be metabolized primarily by phase II conjugation reactions.